Cu-Catalyzed direct cyanation of terminal alkynes with AMBN or AIBN as the cyanation reagent1. Issue 72 (18th September 2015) - Rong, Guangwei; Mao, Jincheng; Zheng, Yang; Yao, Ruwei; Xu, Xinfang
<x xml:space="preserve">Abstract</x> A Cu(ii)-catalyzed direct cyanation of terminal alkynes was reported with broad substrate generality in moderate to high yield.